NON-TECHNICAL SKILLS DEVELOPMENT OF PROSPECTIVE COUNSELORS - Yessika Nurmasari (OPTIMA: Journal Of Guidance and Counseling, 2023)
Counselors in the field get moderate to low ratings in terms of guidance and counseling services as a whole. Performance is considered not in accordance with the competencies that should be possessed. Before entering the world of work, prospective counselors need to prepare themselves by practicing non-technical skills. Non-technical skills have a bigger role than technical skills at work. The research uses a qualitative method, namely a literature review with multiple hermeneutic analysis. The non-technical skills of prospective counselors are divided into two general non-technical skills as a form of adaptation to entering the world of work and microcounseling, namely non-technical skills to optimize guidance and counseling services. Development of non-technical skills is carried out by integrating academic and non-academic. Recommendations for universities providing non-technical skills development services; prospective counselors recognize the need to develop non-technical skills; future researchers can examine techniques that are effective in teaching and training non-technical skills.